Relação entre empatia, atitude implícita e sobrecarga em cuidadores de idosos formais e informais - Maximiano-Barreto, Madson Alan (Universidade Federal de São Carlos, 2020)
Introduction: The number of elderly in Brazil is increasing, as the prevalence of chronic diseases in this population, consequently there is a greater demand for caregivers. The burden is highly prevalent among caregivers and the studies indicate that there is a relationship between the severity of the condition, the level of dependence of the elderly and the burden of the caregiver. Although the caregiver-elderly interaction is well studied, the relationship between empathy, implicit attitude and burden in formal and informal caregivers is still little explored in the literature. Objective: To analyze the relationship between empathy, implicit attitude, and burden in formal and informal caregivers who work in the elderly's home. Method: This is a cross-sectional study with a non-probabilistic sample of 111 elderly caregivers, 54.6% (n=60) informal and 45.4% (n=51) formal. The following instruments were used for data collection: a questionnaire to characterize the care and sociodemographic profile of caregivers, Zarit Burden Inventory (ZBI), Patient Health Questionnaire-9 (PHQ-9), Self-Report Questionnaire-20 (SRQ-20), Multidimensional Interpersonal Reactivity Scale (MIRS), Functional Assessment Questionnaire (FAQ) and Implicit Association Test (IAT). Results: The sample consisted of caregivers aged 19-79 years with a mean age of 45.36 years (SD: ± 14.53). There was a positive correlation between EMRI-Total and burden (ZBI) (r=0.203, p=0.033), depressive symptoms (PHQ-9) (r=0.341; p<0.001) and neuropsychiatric (SRQ-20) (r=0.355; p<0.001). The burden also presented a moderate positive correlation with depressive symptoms (r=0.551, p=0.001) and neuropsychiatric (r=0.606, p=0.001). The IAT pointed out that the caregivers presented an implicit preference for the young public (score D = 0.23, SD ± 0.36). However, there were no significant differences between the IAT scores and the other variables analyzed. Conclusion: The high level of empathy, mainly in the emotional domain, can have consequences for caregivers of the formal and informal elderly, such as burden, neuropsychiatric disorders, and depression. Thus, it is important to think about training for elderly caregivers to balance the levels of empathy in the emotional and cognitive domains and to minimize the consequences for the elderly and the caregiver.
Relationship between empathy, implicit attitude and burden in caregivers of older adults of formal and informal
Keywords: Cuidador; Empatia; Sobrecarga; Atitude Implícita; Gerontologia; Caregiver; Empathy; Burden; Implicit attitude; Gerontology; CIENCIAS DA SAUDE::MEDICINA::PSIQUIATRIA